Carotenogenesis in cyanobacteria: CruA/CruP-type and CrtL-type lycopene cyclases - Takaichi, Shinichi; Sugiyama, Kenjiro (Journal of general and applied microbiology, 2020)
Cyanobacteria are oxygenic photoautotrophic prokaryotes containing chlorophylls and carotenoids, and the latter play important roles in light-harvesting, protection of excess light, assembly of pigment-protein complexes, and stabilization of lipid membranes. Cyanobacteria produce many kinds of carotenoids, such as β-carotene, zeaxanthin, echinenone, and myxol glycosides, which have a cyclic structure at one or both end(s). Cyclization of lycopene is a branch point in carotenoid biosynthesis to β-carotene and γ-carotene. Two types of lycopene cyclases, CruA/CruP-type and CrtL-type, are functionally confirmed in only five species, while homologous genes are found in the genomes of most cyanobacteria. This review summarizes the carotenogenesis pathways and the functional enzymes along with genes, focusing particularly on the cyclization of lycopene by distinct types of lycopene cyclases in cyanobacteria.